2017
DOI: 10.1515/amm-2017-0347
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion of Magnesium Alloy AZ31 with Additive Lithium

Abstract: The purpose of performed tests was evaluation of resistance to electrochemical corrosion of extruded magnesium alloy AZ31 with additive of 4.5% Li. Corrosion tests were performed in 0.01-2.0 M NaCl solutions. Potentiodynamic tests enabled to register polarisation curves. With application of stereoscopic microscope Nikon SMZ745T and electron scanning microscope Hitachi S-4200, the surface of the alloy was observed after immersion tests performed in 1-6 days. Results of performed tests prove explicitly deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was also observed that the addition Li decreased recovery temperature and improved formability of magnesium alloys. The alloy with 4.5 wt.% Li was susceptible to localized degradation in NaCl [43].…”
Section: Polymers Composites Alloys and Special Materialsmentioning
confidence: 99%
“…It was also observed that the addition Li decreased recovery temperature and improved formability of magnesium alloys. The alloy with 4.5 wt.% Li was susceptible to localized degradation in NaCl [43].…”
Section: Polymers Composites Alloys and Special Materialsmentioning
confidence: 99%